Between expectations and reality: self-narration of the planning profession among selected Polish groups of students and professionals. The voice from Poznań - Kotus, Jacek (Bulletin of Geography. Socio-economic Series, 2024)
Strategies for teaching and practising the planning profession have been discussed in the literature for a few decades in what looks like a never-ending story. Nevertheless, this debate is now more important than ever. It seems that planning education and the profession of planners may be a key link in stopping negative changes on the Earth in the 21st century. The article aims to recognize the self-narration of those in planning education and the planning profession in one of the educational hubs of planning in Poland, namely, Poznań. From the perspective of planners’ self-narratives, during five focus group interviews, it transpires that the visions and requirements of the contemporary planning profession as presented in the literature are not always easy to implement in practice (Note).